'She knew he would murder her’: The role of the media in the reconstruction of intimate femicide (Journal of Comparative Social Work, 2018)
The media play a central role in the social construction of intimate femicide, and therefore the news coverage of femicide can contribute to social awareness and the response policies of institutions which deal with this crime. The current study analyses the differences in Israeli newspapers’ framing of femicide committed by members of ethnic groups between the years 2005-2014. The analysis shows that the social construction of intimate femicide reflects the intersection between gender, social class and ethnic origin. The findings suggest that news coverage fills a key role in the perpetuation of the structure of dominance, gender and social class, and that the overall coverage of femicide is mainly episodic and described in personalized terms, rather than within a thematic frame. This study provides new insight into the media’s role in shaping the social denial of this crime, and sheds light on how the prevalent discourse inhibits participants from taking responsibility.